Acute primary testicular failure due to radiotherapy increases risk of severe postoperative adverse events in rectal cancer patients. Issue 1 (January 2020) - Tapper, John; Arver, Stefan; Holm, Torbjörn; Bottai, Matteo; Machado, Mikael; Jasuja, Ravi; Martling, Anna; Buchli, Christian
Abstract: Aim: The aim of this study is to analyze postoperative adverse events (AE) in relation to acute primary testicular failure after radiotherapy (RT) for rectal cancer. Method: This relation was assessed in 104 men, included in a previous prospective cohort study of men treated with surgical resection of the rectum for rectal cancer stage I-III. Postoperative AE were graded according to Clavien-Dindo (2004). Grade 3 or more was set as cut-off for severe postoperative AE. The impact of primary testicular failure on postoperative AE was related to the cumulative mean testicular dose (TD) and the change in Testosterone (T) and Luteinizing hormone (LH) sampled at baseline and after RT. Results: Twenty-six study participants (25%) had severe postoperative AE. Baseline characteristics and endocrine testicular function did not differ significantly between groups with (AE+) and without severe postoperative AE (AE-). After RT, the LH/T-ratio was higher in AE+, 0.603 (0.2–2.5) vs 0.452 (0.127–5.926) (p = 0.035). The longitudinal regression analysis showed that preoperative change in T (OR 0.844, 95% CI 0.720–0.990, p = 0.034), LH/T-ratio (OR 2.020, 95% CI 1.010–4.039, p = 0.047) and low T (<8 nmol/L, OR 2.605, 95 CI 0.951–7.139, p = 0.063) were related to severe postoperative AE. Conclusion: Preoperative decline in T due to primary testicular failure induced by preoperative RT could be a risk factor regarding short-term outcome of surgery in men with rectal cancer.